"Going to Law": Reflections on Law, Religion, and Mitra Sharafi's Law and Identity in Colonial South Asia. Issue 4 (2nd October 2017) - Sullivan, Winnifred Fallers
Abstract : This essay explores religion's need for law, comparing the story told in Mitra Sharafi's Law and Identity in Colonial South Asia (2014)—about the virtual hijacking of British colonial law to serve the communal religious needs of Parsis in colonial India—to other contexts in which secular and religious legal systems have built symbiotic relationships, including in the United States and Thailand. It concludes by urging a reweaving of religious and legal histories after the critique of secularism and its shadows, separationism, and antinomianism.